VLSI Design of a Variable-Length FFT/IFFT Processor for OFDM-Based Communication Systems - Kuo, Jen-Chih; Wen, Ching-Hua; Lin, Chih-Hsiu; Wu, An-Yeu (EURASIP journal on advances in signal processing, 2003)
The technique of orthogonal frequency division multiplexing (OFDM) is famous for its robustness against frequency-selective fading channel. This technique has been widely used in many wired and wireless communication systems. In general, the fast Fourier transform (FFT) and inverse FFT (IFFT) operations are used as the modulation/demodulation kernel in the OFDM systems, and the sizes of FFT/IFFT operations are varied in different applications of OFDM systems. In this paper, we design and implement a variable-length prototype FFT/IFFT processor to cover different specifications of OFDM applications. The cached-memory FFT architecture is our suggested VLSI system architecture to design the prototype FFT/IFFT processor for the consideration of low-power consumption. We also implement the twiddle factor butterfly processing element (PE) based on the coordinate rotation digital computer (CORDIC) algorithm, which avoids the use of conventional multiplication-and-accumulation unit, but evaluates the trigonometric functions using only add-and-shift operations. Finally, we implement a variable-length prototype FFT/IFFT processor with TSMCm 1P4M CMOS technology. The simulations results show that the chip can perform (-)-point FFT/IFFT operations up to operating frequency which can meet the speed requirement of most OFDM standards such as WLAN, ADSL, VDSL (), DAB, and-mode DVB.